IRONY IN CHARLES DICKEN'S OLIVER TWIST - Ika Kana Trisnawati; Sarair Sarair; Maulida Rahmi (Englisia: Journal of Language, Education, and Humanities, 2016)
This paper describes the types of irony used by Charles Dickens in his notable early work, Oliver Twist, as well as the reasons the irony was chosen. As a figurative language, irony is utilized to express one’s complex feelings without truly saying them. In Oliver Twist, Dickens brought the readers some real social issues wrapped in dark, deep written expressions of irony uttered by the characters of his novel. Undoubtedly, the novel had left an impact to the British society at the time. The irony Dickens displayed here includes verbal, situational, and dramatic irony. His choice of irony made sense as he intended to criticize the English Poor Laws and to touch the public sentiment. He wanted to let the readers go beyond what was literally written and once they discovered what the truth was, they would eventually understand Dickens’ purposes.